Associations between adolescent siblings' relationship quality and similarity and differences in values - Kretschmer, Tina; Pike, Alison (Journal of family psychology, 2010)
Theoretically framed by a self-determination perspective on value acquisition and taking into account research into sibling similarity and differences, the current study examined links between sibling relationship quality and adolescents' intrinsic values (benevolence and universalism) and extrinsic values (power, achievement, and materialism). Positive sibling experiences were expected to be positively linked to intrinsic values and negatively linked to extrinsic values, and negative experiences were hypothesized to fuel extrinsic values and thwart intrinsic values. Using a sample of 205 adolescent sibling pairs (older children M = 17.61 years, younger children M = 14.63 years) and multilevel modeling, we assessed within- and between-dyads differences to identify whether the sibling relationship functions as a correlate of values in a similar or different way for 2 siblings. Although siblings were not very similar in their values, sibling competition predicted sibling similarity in higher levels of extrinsic values and lower levels of intrinsic values. Implications for value acquisition research that so far has focused almost solely on parents and failed to acknowledge other processes within families are discussed. © 2010 American Psychological Association.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Sibling relationship; Sibling similarity and difference; Value acquisition